Revisiting Iraq: Change and Continuity in Familial Relations of Iraqi Refugees in Copenhagen - Holm Pedersen, Marianne (Anthropologica, 2022)
For refugees, their coùntry of origin often provides a strong source of belonging and identity, yet many refugees can only maintain infrequent contacts with it. This article inves- tigates how the sudden increase in relations with Iraq after Sad- dam Hussein’s fall affected Iraqi refugee women and their fam- ilies in Copenhagen, Denmark. It shows that, while renewed transnational practice in some ways allowed the women to re- create links to their relatives and their places of origin, thus affirming their Iraqi identity, it also raised questions about pre- vious notions of relatedness and belonging and created a stronger sense of belonging in Denmark.